THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENGLISH LANGUAGE TEACHING - MAXBUBA SULTANOVA SULTANBEKOVNA (TADQIQOTLAR, 2026)
ABSTRACT This study examines the role of Artificial Intelligence (AI) in English language teaching and learning. The rapid development of AI technologies has transformed educational practices by providing innovative tools for language instruction, assessment, and personalized learning. AI-powered applications, including intelligent tutoring systems, chatbots, speech recognition software, automated writing evaluation tools, and adaptive learning platforms, enable learners to improve their language skills more efficiently and interactively. The research highlights how AI enhances the teaching of English by supporting vocabulary acquisition, grammar practice, pronunciation improvement, reading comprehension, writing development, and speaking fluency. Furthermore, AI assists teachers in managing classroom activities, monitoring student progress, and providing individualized feedback. The integration of AI into language education contributes to increased learner motivation, engagement, and autonomy.